Full facial retransplantation in a female patient—Technical, immunologic, and clinical considerations. Issue 10 (22nd July 2021) - Kauke, Martin; Panayi, Adriana C.; Safi, Ali‐Farid; Haug, Valentin; Perry, Bridget; Kollar, Branislav; Nizzi, Marie‐Christine; Broyles, Justin; Annino, Donald J.; Marty, Francisco M.; Sinha, Indranil; Lian, Christine G.; et al.
Abstract : There is limited experience with facial retransplantation (fRT). We report on the management of facial retransplantation in a facial vascularized composite allotransplant recipient following irreversible allograft loss 88 months after the first transplant. Chronic antibody‐mediated rejection and recurrent cellular rejection resulted in a deteriorated first allograft and the patient underwent retransplantation. We summarize the events between the two transplantations, focusing on the final rejection episode. We describe the surgical technique of facial retransplantation, the immunological and psychosocial management, and the 6‐month postoperative outcomes. Removal of the old allograft and inset of the new transplant were done in one operation. The donor and recipient were a good immunological match. The procedure was technically complex, requiring more proximal arterial anastomoses and an interposition vein graft. During the first and second transplantation, the facial nerve was coapted at the level of the branches. There was no hyperacute rejection in the immediate postoperative phase. Outcomes 6 months postoperatively are promising. We provide proof‐of‐concept that facial retransplantation is a viable option for patients who suffer irreversible facial vascularized composite allograft loss. Abstract : The authors describe the technical, immunological, and clinical challenges pertaining to facial retransplantation.